The Factor Time in Fetal Heart Rate Monitoring and the Detection of Acidosis Using the WAS Score - Roemer, V. M.; Walden, R. (Zeitschrift für Geburtshilfe und Neonatologie, 2014)
Background: Using the naked eye evaluation of fetal heart rate (fhr) patterns remains difficult and is not complete. Computer-aided analysis of the fhr offers the opportunity to analyze fhr patterns completely and to detect all changes due to hypoxia and acidosis. It was the goal of this study to analyze the factor time in fetal monitoring and to evaluate the association between the fhr and the actual pH values in arterial umbilical blood.Methods: During a period of 11 years the FHR signals (i. e., the R-R interval of the F-ECG) of 646 fetuses were recorded with a CTG and simultaneously by a computer. The computer files were analyzed thereafter, i. e., the results did not influence our clinical management. To enter the study, all fetuses must have been delivered by the vaginal route – in consequence without a significant loss of fhr signals. During forceps and/or vacuum deliveries recordings were continued. If necessary a new electrode was inserted. In this study recordings of fetuses with chorioamnionitis, tracings of malformed neonates and tracings shorter than 30 min were excluded. Thus 484 recordings were left. We used our own computer programs written in MATLAB (USA). 3 parameters were determined electronically: 1) the mean fetal frequency [fhf, (bpm)], 2) the number of turning points (N/min) in the fhr, which we called ‘microfluctuation’ (micro) and 3) the oscillation amplitude, oamp (bpm). Measurements of the acid-base variables from arterial (UA) and venous (UV) blood were performed using RADIOMETER equipment (ABL500) and trained personnel. However, only the actual pHUA values were used in this study. To detect the influence of hypoxia and acidosis, all 484 cases were separated into 7 groups according to the actual pHUA value: 55 fetuses lying in a small non-acidotic “pH-window” (pHUA=7.290–7.310, mean=7.300±0.008) were used as ‘controls’.Results: In humans fhf, micro and the oamp behave differently during the last 30 min of delivery and with different fetal pHUA values: micro is early (at 0 min) decreased with fetal acidemia and is steadily deceasing (68–40 N/min) during vaginal delivery; the oamp – mainly due to decelerations – is increased from 35 up to 70 bpm during the last 30 min. Hypoxia and acidosis increase the amplitude and duration of decelerations; finally fhf shows only an insignificant reaction to acidemia but is decreased (from 135 to 110 bpm) overall with the course of time. Therefore the 3 characteristics of the fhr might be ranged according to their decreasing sensitivity to acidemia as follows: 1) fetal microfluctuation, 2) oscillation amplitude and 3) mean frequency. The 3 components of the fhr were used to invent and apply a score named the WAS score. This score increases the association between the actual pHUA values and the activity of the fetal heart. The 3 variables of the fhr mentioned above were rated differently; the 3 factors necessary to achieve this were computed electronically using an optimization program. The result is the WAS score: WAS=mean [frq*ff(vj) * micro*fm (vj)/oamp*fa(vj)]j=1,30. Using the last 30 min of delivery the correlation coefficient r of this score with pHUA reaches 0.645, P<< 0.001. The regression is linear in our 484 cases.Conclusions: Microfluctuation is the most sensible variable of the fetal heart followed by the oscillation amplitude and mean frequency. The WAS score offers the best correlation with the actual pH values measured in arterial umbilical blood.
Keywords: time in fetal monitoring; WAS score; fetal heart frequency; microfluctuation; oscillation-amplitude